2006
DOI: 10.1128/aac.50.4.1510-1517.2006
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional Volumetric Imaging of Pulmonary Infiltrates for Measuring Therapeutic Response to Antifungal Therapy in Experimental Invasive Pulmonary Aspergillosis

Abstract: Pulmonary infiltrates in neutropenic hosts with invasive pulmonary aspergillosis are caused by vascular invasion, hemorrhagic infarction, and tissue necrosis. Monitoring the dynamics of pulmonary infiltrates of invasive aspergillosis is an important tool for assessing response to antifungal therapy. We, therefore, introduced a multidimensional volumetric imaging (MDVI) method for analysis of the response of the volume of pulmonary infiltrates over time to antifungal therapy in experimental invasive pulmonary a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…In neutropenic rabbits, pulmonary disease is characterized by intensive hyphal growth and high fungal burden; by comparison, in corticosteroid-treated animals, pulmonary inflammation and decreased fungal burden are the hallmarks [48]. Given the association between the GM levels and the pulmonary tissue burden of A. fumigatus not only in animal models [27,28], but also in the clinical setting, it seems to be the case that the host's immune status may play a role in the results of the assay [30]. Therefore, the sensitivity of the assay is dependent on the cut-off used for positivity, concomitant antifungal therapy, and the population studied.…”
Section: Sensitivitymentioning
confidence: 97%
See 1 more Smart Citation
“…In neutropenic rabbits, pulmonary disease is characterized by intensive hyphal growth and high fungal burden; by comparison, in corticosteroid-treated animals, pulmonary inflammation and decreased fungal burden are the hallmarks [48]. Given the association between the GM levels and the pulmonary tissue burden of A. fumigatus not only in animal models [27,28], but also in the clinical setting, it seems to be the case that the host's immune status may play a role in the results of the assay [30]. Therefore, the sensitivity of the assay is dependent on the cut-off used for positivity, concomitant antifungal therapy, and the population studied.…”
Section: Sensitivitymentioning
confidence: 97%
“…Subsequent studies of experimental IPA in persistently neutropenic rabbits demonstrated a direct quantitative relationship between serum levels of GM, and other markers of severity of infections: residual pulmonary burden (logCFU/g), lung weights, pulmonary infarct scores and CT scan infiltrate index [26][27][28].…”
Section: Galactomannan Antigen: Structure and Immunochemistrymentioning
confidence: 98%
“…Many clinically important issues, however, still remain unanswered: does the assay correlate with fungal burden and what is the behavior of the test over time [13,14]? What is the impact of antimold prophylaxis or therapy on test performance [15,16 ]?…”
Section: Detection Of Galactomannanmentioning
confidence: 99%
“…Computerized tomography was performed to measure the response of pulmonary infiltrates to antifungal therapy (38). A semiautomatic method was then used to measure the volume of lung lesions, as previously described (27).…”
Section: Methodsmentioning
confidence: 99%